Uncompromising : how an unwavering commitment to your why leads to an impactful life and a lasting legacy - White, Steven A. (Ascent Audio, 2022)
Uncompromising explores seven pathways to help you identify and live your why-leading to an impactful life and a lasting legacy. Steve White's path from the housing projects to president of Comcast West was punctuated by defining-and often heart-wrenching-moments. Moments that helped him identify what matters most and how he positively made a difference in his life and in those around him. As one of four boys raised by a single mother, Steve's life could easily have taken a different path. Instead, armed with his mother's determination that her sons make a better life for themselves and his own refusal to be shaped by his circumstances, Steve forged a path to extraordinary professional and personal achievement. Steve's lessons from every stage of life, and the people who influenced him along the way, form the basis of his overarching message: An uncompromising life is one where you stay true to what is important to you, what you believe in, and what you love. This leads to more fulfillment, purpose, and a lasting legacy. Steve's hard-won insights will help you pursue what matters most and discover where you can make the biggest difference.